Género Textil Tejido a Partir del Pelaje canino de la Raza Alaskan Malamute - Santiana García, Erika Tatiana (2023)
The development of a textile genre from the hair of Alaskan Malamute dogs has as its main purpose that the yarn made with the hair of these dogs, when woven as raw material, can be used in the fashion industry in general, since it for years the textile genres that have been obtained from traditional fibers such as sheep and alpacas and even from artificial fibers. To determine the feasibility of producing a woven textile from the fiber of the dog's hair, a protocol for the visual and physical analysis of the wool was carried out, applying interviews to the breeders of these dogs, as well as a laboratory analysis. consulted designers and textile engineers through a survey that allowed us to know how accepted this new textile genre will be in the fashion industry, spinning was carried out using artisan techniques with weavers from Salasaca, to later weave hats and scarves with hair thread of the Alaskan Malamute. Definitely from this research project it is intended to give way to the development of unconventional fibers in order to be applied in fashion as long as it meets the comfort requirement that the application in clothing demands